KEGIATAN LAPANGAN PROGRAM “Creative Action Camp: Pengembangan Karakter Inovatif melalui Experiential Learning” - Anggita Maharani; Nailah Amalia Fatihah; Izza Yulfana Khidismiya; Seftia Amanda Yustika (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This field activity aims to develop innovative character among rural youth through an experiential learning approach in the program "Creative Action Camp: Development of Innovative Character through Experiential Learning". Innovative character includes the ability to think creatively, take initiative, solve problems, and generate new solutions in facing various situations. This activity involved 13 participants from the rural youth community divided into three groups. The method used was experiential learning through a series of group games, namely Mission Without Leader, Save The Egg, Problem Solving Race, and 3-Minute Spontaneous Idea. Evaluation was conducted through observation of participant activeness, collaboration skills, courage in expressing ideas, creativity, and initiative-taking ability, concluding with a reflection session. The results showed that all participants demonstrated high enthusiasm and developed five indicators of innovative character, namely initiative, creativity, collaboration, communication, and courage in decision-making. These findings were reinforced by reflection results indicating that participants were able to connect their experiences during the activity with daily life. Thus, the experiential learning approach proved effective in supporting the development of innovative character among rural youth and can serve as an alternative learning method relevant for sustainable implementation.